Open randomised trial of the (Arabin) pessary to prevent preterm birth in twin pregnancy with health economics and acceptability: STOPPIT-2—a study protocol. Issue 12 (6th December 2018) - Norman, Jane E; Norrie, John; Maclennan, Graeme; Cooper, David; Whyte, Sonia; Cunningham Burley, Sarah; Smith, Joel B E; Shennan, Andrew; Robson, Stephen C; Thornton, Steven; Kilby, Mark D; Marlow, Neil; et al.
Abstract : Introduction: The STOPPIT-2 study aims to determine the clinical utility of the Arabin cervical pessary in preventing preterm birth in women with a twin pregnancy and a short cervix, about which there is current uncertainty. STOPPIT-2 will resolve uncertainty around effectiveness for women with a twin pregnancy and a cervical length of 35 mm or less, define adverse effects, ascertain acceptability and estimate National Health Service costs and savings. Methods: STOPPIT-2 is a pragmatic multicentre open-label randomised controlled trial. Consenting women with twin pregnancy will have an transvaginal ultrasound scan of their cervical length performed between 18+0 and 20+6 weeks' gestation by an accredited practitioner: women with a cervical length of ≤35 mm will be eligible for inclusion in the treatment phase of the study. The intervention by the insertion of the Arabin cervical pessary will be compared with standard treatment (no pessary). The primary outcomes are (obstetric) spontaneous onset of labour for the mother leading to delivery before 34 weeks' gestation and (neonatal) a composite of specific adverse outcomes or death occurring up to the end of the first 4 weeks after the estimated date of delivery to either or both babies. We plan to recruit 500 women in the treatment phase of the study. Assuming a treatment effect of 0.6, and background rates of 35% and 18%, respectively, for each of the primary outcomes, our study has 85% power to detect a difference between the intervention and the control groups. Analysis: Data will be analysed on the intention-to-treat principle. Ethics: STOPPIT-2 was approved by the South East Scotland Ethics Committee 02 on 29 August 2014, reference number 14/SS/1031 IRAS ID 159610. Dissemination: Peer reviewed journals, presentations at national and international scientific meetings. Trial registration number: ISRCTN98835694 and NCT02235181 .